정면 3칸 팔작지붕 불전의 처마 곡선과 지붕 길이 조절에 관한 연구 - 위소연; 성대철; 신웅주; Wi, So-Yeon; Sung, Dae-Chul; Shin, Woong-Ju (건축역사연구 : 한국건축역사학회논문집, 2017)
It is difficult to build a hipped and gable roof in slender rectangular type due to restraint in variation of lateral length caused by gongpo arranged on the side, purlin space and the form of gable part and aesthetical effect of chunyeo maru. Against this backdrop and with the assumption that this phenomenon is more apparent in roofs of three-bay-kan Buddhist temples with the hipped and gable roof among national treasure Buddhist temples, this study has aimed to prove that a roof can be built in a less slender rectangular type than that of flat form and to present the building methodology and found the following findings. First, The ratio of lateral to longitudinal length of the roof has been adjusted by protruding the chunyeo and the method of adjusting the ratio of lateral to longitudinal length of the roof is considered to be determined depending on the availability of woods to be used in chunyeo. Second, in order to symmetrically arrange the edge of the roof, which is critical from the perspective of construction morphology, the chunyeo angle has been intentionally adjusted to reduce the gap of length between the front roof and the lateral roof. To sum up, the characteristic of the hipped and gable roof, which is difficult to be built in slender rectangular type, is more clearly shown in the roof and it is identified that the length of the front roof and the lateral roof has been intentionally adjusted to achieve the symmetrical arrangement of roofline of the roof edge.